Effectiveness of paliperidone depot injection in seriously violent men with comorbid schizophrenia and dissocial personality disorder in a UK high-security hospital. Issue 5 (May 2017) - Mortlock, Anna-Marie; Larkin, Fintan; Ross, Callum C.; Gupta, Nitin; Sengupta, Samrat; Das, Mrigendra
Background: High-security hospital patients are often complex in presentation and are characterized by treatment resistance, medication nonadherence and history of violence. Paliperidone is licensed both as an oral and depot antipsychotic medication in the treatment of schizophrenia. Clinical trials have shown that paliperidone depot is well tolerated with similar efficacy to risperidone depot but with additional practical advantages. Whilst data exist for the effectiveness of paliperidone palmitate (PP), there are no studies involving patients in forensic settings or those with comorbid personality disorder. Our aim was to evaluate the effectiveness of PP on violence, aggression and personality disorder symptoms. Methods: This project was a retrospective service evaluation involving 11 patients, carried out in a high-security hospital. A combination of patient records and interviews with the treating consultant psychiatrist were used to ascertain a Clinical Global Impression (CGI) score, the effect of PP on specific personality disorder symptom domains (cognitive-perceptual, impulsive-behavioural dyscontrol and affective dysregulation) and incidents of violence and aggression. Engagement with occupational and psychological therapies was also evaluated. Metabolic parameters were reviewed. Results: A total of 6 out of 11 patients continued on PP, most of whom had schizophrenia and dissocial personality disorder with histories of violence. All showed improvement in the CGI score with associated benefits in the three personality symptom domains. Overall, two patients demonstrated a reduction in the risk of violence. There was improvement in engagement with occupational therapy and psychological work. No significant effects on metabolic parameters were noted although hyperprolactinaemia, albeit asymptomatic, was consistently recorded. Conclusions: This pragmatic service evaluation of a small but complex patient group demonstrated, for the first time, that PP was effective in reducing violence as well as improving personality pathology across all dimensions: a finding which could have significant implications for management of such high-security patients.